A case of HIV associated cryptococcal nephritis: Ultrastructural findings and literature review. (4th March 2018) - Flowers, Ashley; Gu, Xin; Herrera, Guillermo A; Gibson, Sandy; King, Judy
ABSTRACT: Acute renal failure in the setting of infection with human immunodeficiency virus can be due to various causes including pre-renal causes such as hypotension, sepsis, and nephrotoxic agents; thrombotic microangiopathy; or direct renal parenchymal infections by opportunistic organisms. We present a case of cryptococcal nephritis in a patient with systemic cryptococcosis and discuss the clinical findings as well as the histological, immunofluorescent, and transmission electron microscopy findings in the renal biopsy.